Pengabdian Masyarakat Membuat Aplikasi Iuran Keuangan - Goenawan, Stephanus Ivan; Natalia, Christine; Wahyu, Marsellinus Bachtiar; Nugroho, Veronica Tirza (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2022)
Along with the rapid development of the times, in all sectors of course it is necessary to follow these developments in order to achieve mutual comfort and safety. The Housing Complex also does not escape to be able to keep up with the times. Every housing estate certainly has activities to collect dues to be able to manage their living environment in a clean, safe and comfortable condition. The financial management of contributions carried out still applies a manual system, so that there is a human error between financial records and the actual evidence is not the same. In addition, with a manual system like this, misunderstandings can arise and the truth is quite difficult to prove due to manual recording. Using the Rapid Application Development method to design a financial management mobile app that has an incremental nature with the intention that the processing time can be done in a short time but still optimally. The data needed will be integrated using Firebase which has a real-time nature so that records can be recorded automatically and existing data is always updated according to existing events. Application design using the JavaScript programming language in the Visual Studio program and integrated with Firebase as a place to process data. Based on testing the system has been designed and can be used properly